2019
DOI: 10.12775/eq.2019.022
|View full text |Cite
|
Sign up to set email alerts
|

Field hospital wastewater treatment scenario

Abstract: In extreme situations with a large number of victims, field hospitals are deployed to provide patients with medical treatment. The large number of patients with different types of medications used generates the problem of hospital waste accumulation, including hospital wastewater (HWW). Wastewater is water having compromised characteristics that adversely affect the environment. Many countries do not have strict regulations regarding the disposal of hospital effluent, which contains pathogens, toxic chemicals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…In work (Evangeliou & Eckhardt, 2020), when studying the real conditions for extinguishing a fire in April 2020 (Ukraine), which lasted 22 days, it is reported that even if fire-fighters remain in the CEZ after trying to extinguish fires, and then return to extinguish another fire the next day, remaining 60% of the time in indoors, the total doses will amount to about 1% of the annual external exposure dose from the background radiation left over from the Chernobyl accident. Nevertheless, even in such a situation, firefighters should be equipped with the necessary respiratory protection, and field hospitals should be organized in places where firefighters are located (Khan et al, 2019a;Khan et al, 2019b) for a quick response in case of deterioration of their health. These hospitals are also recommended to be equipped with inexpensive mobile filters that absorb toxic gases, for example based on composite films (Mozaffari et al, 2021).…”
Section: Discussion About Risks For Fire Liquidators and Contaminated Areas' Residentsmentioning
confidence: 99%
“…In work (Evangeliou & Eckhardt, 2020), when studying the real conditions for extinguishing a fire in April 2020 (Ukraine), which lasted 22 days, it is reported that even if fire-fighters remain in the CEZ after trying to extinguish fires, and then return to extinguish another fire the next day, remaining 60% of the time in indoors, the total doses will amount to about 1% of the annual external exposure dose from the background radiation left over from the Chernobyl accident. Nevertheless, even in such a situation, firefighters should be equipped with the necessary respiratory protection, and field hospitals should be organized in places where firefighters are located (Khan et al, 2019a;Khan et al, 2019b) for a quick response in case of deterioration of their health. These hospitals are also recommended to be equipped with inexpensive mobile filters that absorb toxic gases, for example based on composite films (Mozaffari et al, 2021).…”
Section: Discussion About Risks For Fire Liquidators and Contaminated Areas' Residentsmentioning
confidence: 99%
“…There were positive results compared to other water treatment techniques because of their high surface area (superface/volume ratio), metal containing nanoparticles, carbonaceous nanomaterials, zeolites and dendrimers and nanofibers. In their paper, [32] discussed a few recently used nanomaterials that are currently used in water treatment, with an emphasis on nano-based adsorbents and filtration membranes.…”
Section: G Ai Techniques In Nanotechnology Fieldmentioning
confidence: 99%
“…Growth of various industries in the world wide has caused soils and water resources pollution [1,2]. A lot of research has been done to find ways to decontamination wastewater.…”
Section: Problem Statement and Analysis Of The Recent Researches And mentioning
confidence: 99%